Pengembangan Kurikulum Pendidikan Agama Islam dan Budi Pekerti di Sekolah Dasar: Penelitian - Novi Nur Sa’diyah; Suparjo (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
One of the important components in education is the curriculum. The educational curriculum contains the vision, mission and objectives of education in a school. The curriculum needs to be developed to be in accordance with the development of the times, so that it produces output that can adapt to the needs of the times. This study aims to describe the process of developing the Islamic Religious Education (PAI) and Character Education curriculum at the Elementary School (SD) level as well as the components of the PAI curriculum implemented at SDN Ajibarang Wetan. The type of research used in this study is qualitative research. The approach used is a descriptive qualitative approach with a case study type. The data in this study were taken at Ajibarang Wetan State Elementary School, Ajibarang District, with the principal, teachers and some students as samples. Every educator must understand the development of the curriculum, because it is the most important pedagogical formulation in the context of education, in the curriculum will be depicted how efforts are made to help students develop their potential in the form of physical, intellectual, emotional, and socio-religious and so on. In this paper will be discussed the basic concepts, components and philosophy of the Islamic Religious Education curriculum.